Age and gender effects of workforce composition on productivity and profits: Evidence from a new type of data for German enterprises - Christian Pfeifer; Joachim Wagner (Contemporary Economics, 2014)
This empirical paper documents the relationship between the composition of a firm's workforce (with a special focus on age and gender) and its performance (productivity and profitability) for a large representative sample of enterprises from manufacturing industries in Germany using newly available, unique data. We find concave age-productivity profiles and a negative correlation of age on firms' profitability. Moreover, our micro-econometric analysis reveals for the first time that the ceteris paribus lower level of productivity in firms with a higher share of female employees does not go hand in hand with a lower level of profitability in these firms.
Keywords: D22; D24; J21; J24; L25; 330; ageing; firm performance; gender; productivity; profitability; Germany